Significance of collateral circulation in managing persistent sciatic artery: Two case reports - Yun, Woo-Sung; Kim, Hyeon Ju; Hwang, Deokbi; Kim, Hyung-Kee (Frontiers in Surgery, 2023)
Persistent sciatic artery (PSA) is a rare congenital anomaly considered an embryologic remnant of the internal iliac artery. Traditionally, the classification systems categorized PSA based on the completeness of PSA and superficial femoral artery (SFA) alongside the origin of PSA. The most common class has been known as type 2a in Pillet–Gauffre classification, meaning complete PSA with incomplete SFA. The mainstay of these patients with limb ischemia has been surgical bypass alongside excision or ligation of PSA aneurysm if present. However, the current PSA classification system does not account for collateral blood flow. Herein, we described two cases of type 2a PSA with distal embolization and explored therapeutic choices for PSA based on collateral presence. The first patient was treated with thromboembolectomy and patch angioplasty, and the second with conservative management. Despite distal embolization in both patients, bypass surgery was avoided, and distal circulation was maintained via collaterals from deep and superficial femoral arteries without increased risk of recurrent embolization. Thus, carefully examining collateral circulation and customized strategy is essential for managing PSA.